Computational Study of the Adsorption of Small Gas Molecules on Pillar[5]arenes. Issue 12 (21st March 2023) - Duy Ho, Quoc; Rauls, Eva
Abstract: The anthropogenic carbon dioxide (CO2 ) that is the main cause of the greenhouse effect has become subject to many studies of gas capture, storage, and separation. P[n]A‐based supramolecular organic frameworks (SOF) have emerged as a promising candidate for capturing and separation of CO2 . Experimental studies show high adsorption rates and selectivity for CO2 over other gases such as methane (CH4 ) and nitrogen (N2 ). [Advanced Materials 26, 7027 (2014)] However, a full understanding of CO2 adsorption in P[n]A is still missing. Using density functional theory (DFT) based calculations, we found that CO2 can be adsorbed by P[5]A in different positions. The most favorable adsorption position is within the cavity of P[5]A. The CO2 molecule adsorbs by forming hydrogen bonds or by π‐π interaction with the benzene rings of P[5]A. Also CH4 and N2 can be physisorbed by P[5]A, but with lower binding energies, which can be explained by the weaker quadrupole moments and polarizabilities of CH4 and N2 . Our investigations are the basis for targeted design and optimization of a potential application of P[5]A in CO2 capture, storage, and separation. Abstract : The adsorption of CO2 at P[5]A were studied by using DFT‐based methods. CO2 can be adsorbed by P[5]A at the cage cavity site and at a hydroxyl group. π‐π interactions and weak hydrogen bonds play the major role in the adsorption at the cavity site and OH groups, respectively. The DOS shows the physical adsorption of CO2 in P[5]A. The adsorption of CO2 in P[5]A is more favorable in comparison with CH4 and N2 .